Enhancing MSMEs’ Innovation Capacity Based on the ISO 56002:2019: A Case Study of the XYZ Perfume Company in Yogyakarta - Prasetiyo, Wildan Guretno; Mubarok, Dadan Abdul Aziz; Sofiati, Nunung Ayu; Ali, Mochammad Mukti; Sajekti, Tjipto (Universitas Airlangga, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia's economy, contributing 60.5% to the Gross Domestic Product (GDP) in 2024. These facts underscore the importance of MSME development as a priority in the Asta Cita of the President of the Republic of Indonesia. However, alongside financial constraints, researchers contend that MSMEs face challenges in competitiveness due to a lack of innovation and creativity. To address this, a standard for innovation capacity needed and ISO 56002:2019 can serve it. Nevertheless, research in this field remains limited, highlighting the need for studies focused on enhancing innovation capacity based on ISO 56002:2019 for Indonesian MSMEs. This qualitative study employs semi-structured interviews with XYZ Perfume Company in Yogyakarta, an MSME actor. The assessment is based on eight factors from the development of ISO 56002:2019 by researchers: (1) Transformative Leadership; (2) Strategic Intention to Innovate; (3) Weight Management for Information; (4) Customer and Market Knowledge; (5) Strategic Technology Management; (6) Organizational Structure; (7) Project Management; and (8) Innovation Performance. The results indicate that XYZ Perfume Company's innovation capacity achieves a qualitatively good rating in Transformative Leadership, Weight Management for Innovation, Customer and Market Knowledge, and Project Management; a moderate rating in Strategic Intention to Innovate and Organizational Structure; and a below-average rating in Strategic Technology Management and Innovation Performance. Strategies for enhancing the innovation capacity of XYZ Perfume Company were formulated. These findings and the proposed strategies serve as a valuable foundation for MSMEs in developing new products.